Dealing with negative life events: differential effects of personal resources, coping strategies, and control beliefs - Jopp, Daniela; Schmitt, Marina (European journal of ageing, 2010)
The study examines the extent to which resources, coping strategies, and control beliefs predict adaptation to negative critical life events. Specifically, we investigated the effects of basic resources (i.e., sociodemographics, cognition, health, social), coping (i.e., assimilative and accommodative coping), and control beliefs (i.e., internal control) as well as their interplay in the context of multiple negative events. Well-being served as an indicator of adaptation. Four hundred and twenty middle-aged participants of the Interdisciplinary Longitudinal Study of Adult Development (ILSE; Schmitt 2006) were assessed at two measurement occasions 4 years apart. Events and coping were assessed via interviews (e.g., assimilative coping: active problem-solving, goal-directed effort, social support; accommodative coping: reevaluation of situation, acceptance, and adjustment of standards). Participants experienced an average of six negative events between measurement occasions. Resources had positive relations to control beliefs, coping, and well-being. More resources were related to fewer negative events experienced later on. More negative events were linked to more coping and poorer well-being. Structural equation models showed that the effect of resources on well-being was mediated by assimilative coping. Subgroup analysis revealed that the beneficial effect of assimilation was restricted to individuals with high internal control beliefs. Although the relationship between events and coping did not differ between both groups, only individuals with high control beliefs benefited from assimilation, perhaps because they coped more effectively. In sum, investigating resources, coping, and control beliefs concurrently allows the identification of more complex effect patterns that enhance the understanding of individual differences in dealing with negative life events.
Gesehen am 14.09.2023